Physical properties, antioxidant capacity, and starch digestibility of cookies enriched with steam-exploded wheat bran - Kong, Feng; Li, Yue; Xue, Di; Ding, Yishuai; Sun, Xiaofan; Guo, Xingfeng; Wang, Wenhao (Frontiers in Nutrition, 2022)
Wheat bran-based food is rich in bioactive compounds, and steam explosion enhanced the nutritional properties of wheat bran. In this study, the potential utilization of steam-exploded wheat bran (SWB) in the formulation of cookie was examined. The influence of steam explosion on the chemical compounds in wheat bran, and effects of SWB on physical property, antioxidant capacity and starch digestibility of cookies were investigated. Results showed that steam explosion facilitated the release of reducing sugar, flavonoids, phenolics substance and amino acid nitrogen in wheat bran, consequently improving its nutritional properties. The reducing sugar, total flavonoids, total phenolics and amino acid nitrogen contents in wheat bran after steam explosion increased by 34.22%, 183.02%, 284.09% and 93.39%, respectively compared with those of native wheat bran. Substitution with SWB to wheat flour mainly induced a higher water, sodium carbonate and sucrose solvent retention capacity, which were positively related to the spread ratio and hardness of cookies. The cookies with more SWB substitution (30 50%) expressed higher spread ratio and hardness than the others. The substitution of SWB caused the changes in antioxidant properties of cookies which related to the phenolics content. The cookies incorporated with SWB showed a higher DPPH radical scavenging activity (16.30% 30.93%) than that of the control (14.74%). SWB might form a matrix barrier to hinder starch digestion thus reducing the digestibility of cookies. The cookies enriched with 30 50% of the SWB exhibited greater physical property and antioxidant capacity but lower starch digestibility than those of other cookies. The results will contribute to expand the application range and improve the quality of bran-rich flour products.